2019
DOI: 10.3847/2041-8213/ab4db3
|View full text |Cite
|
Sign up to set email alerts
|

Half-mass Radii of Quiescent and Star-forming Galaxies Evolve Slowly from 0 ≲ z ≤ 2.5: Implications for Galaxy Assembly Histories*

Abstract: We use high-resolution, multi-band imaging of ∼16,500 galaxies in the CANDELS fields at 0 z ≤ 2.5 to study the evolution of color gradients and half-mass radii over cosmic time. We find that galaxy color gradients at fixed mass evolve rapidly between z ∼ 2.5 and z ∼ 1, but remain roughly constant below z ∼ 1. This result implies that the sizes of both star-forming and quiescent galaxies increase much more slowly than previous studies found using half-light radii. The half-mass radius evolution of quiescent gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 45 publications
9
65
0
Order By: Relevance
“…In the left panel of Figure 6 we reproduce the results reported in Suess et al (2019b) for quiescent galaxies with masses log(𝑀 ★ /M )>10.1, black dots with error bars. The strong 𝑅 50M /𝑅 50𝑟 evolution observed at 𝑧 1 appears to flatten at 𝑧 < 1.…”
Section: Comparison With Direct Observationssupporting
confidence: 65%
See 3 more Smart Citations
“…In the left panel of Figure 6 we reproduce the results reported in Suess et al (2019b) for quiescent galaxies with masses log(𝑀 ★ /M )>10.1, black dots with error bars. The strong 𝑅 50M /𝑅 50𝑟 evolution observed at 𝑧 1 appears to flatten at 𝑧 < 1.…”
Section: Comparison With Direct Observationssupporting
confidence: 65%
“…This is because the Υ ★ gradients became more negative with time. In Suess et al (2019b), the authors extended their analysis to 𝑧 ≈ 0.25 by adding ∼ 9000 CANDELS galaxies at 𝑧 ≤ 1.0 and found that the 𝑅 50M -to-𝑅 50L ratios decrease slower or remain constant at 𝑧 ∼ 1.…”
Section: Comparison With Direct Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, colors are not sensitive to IMF differences, so their methodology does not, in fact, it cannot account for IMF variations (or, for that matter, the age-metallicity degeneracy), which we showed may be the dominant driver of M * /L gradients at low-z. In this context, it is useful to compare our Figure 10 with the horizontal dashed line in the right hand panel of Figure 1 in Suess et al (2019b). Our analysis, which is sensitive to IMF-driven gradients, shows that Re, * /Re decreases from 0.8 to 0.5 as M * increases from 3 × 10 10 M to 5 × 10 11 M , whereas their analysis returns Re, * /Re ∼ 0.8 at all M * .…”
Section: Comparison With Quiescent Galaxies At High Redshiftmentioning
confidence: 99%